2014
DOI: 10.1021/jo501714f
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Down the Reactivity of λ3-Iodanes: The Impact of Structure and Bonding on Competing Reaction Mechanisms

Abstract: The functionalization of arenes via diaryliodonium salts has gained considerable attention in synthesis, as these compounds react under mild conditions. Mechanistic studies have shown that the formation of corresponding λ(3)-iodane intermediates takes a key role, as they determine the course and selectivity of the reaction. Bridged diaryliodonium salts, featuring a heterocyclic moiety involving the iodine atom, were shown to exhibit a distinctly different reactivity, leading to different products. These produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
(53 reference statements)
2
28
0
Order By: Relevance
“…[12,13] The possibility of an SET mechanism is explored also for the trifluoromethylation of MeCN. Unlike the product of the first step of MeCN-trifluoromethylation, 2, phenyl trifluoromethyl thioether (7) does not represent a reactive intermediate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12,13] The possibility of an SET mechanism is explored also for the trifluoromethylation of MeCN. Unlike the product of the first step of MeCN-trifluoromethylation, 2, phenyl trifluoromethyl thioether (7) does not represent a reactive intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…). The electronic and structural properties leading to the distinct reactivity of reagent 1 have been the topic of earlier studies …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This functional group displays a high degree of chemoselectivity, as demonstrated, for example, by an octapeptide derived from Sandostatin, or by co‐enzyme A . Although the chemistry of iodanes is well established, only recent computational studies revealed the mechanistic versatility of λ 3 ‐iodanes, reminiscent of that of transition metals . We previously investigated the electronic and structural properties leading to the distinct reactivity of reagent 1 as well as polar mechanistic details in combination with N ‐ and S ‐nucleophiles .…”
Section: Introductionmentioning
confidence: 99%
“…Although the chemistry of iodanes is well established, only recent computational studies revealed the mechanistic versatility of λ 3 ‐iodanes, reminiscent of that of transition metals . We previously investigated the electronic and structural properties leading to the distinct reactivity of reagent 1 as well as polar mechanistic details in combination with N ‐ and S ‐nucleophiles . Thus, the activation of reagent 1 by protonation is essential .…”
Section: Introductionmentioning
confidence: 99%